Poly(2-carboxyethyl acrylate-co-ethylene glycol dimethacrylate) monolithic precursor. Part II. Carbodiimide assisted post-polymerization modification with tris and d-Glucamine for use in hydrophilic interaction capillary liquid chromatography. Issue 10 (15th June 2018) - Alharthi, Sarah; El Rassi, Ziad
Abstract: A carboxylated precursor monolith (carboxy monolith), namely poly(2-carboxyethyl acrylate- co -ethylene glycol dimethacrylate), was prepared by the in situ co-polymerization of 2-carboxyethyl acrylate (CEA) with ethylene glycol dimethacrylate (EDMA), see the preceding article in this issue. This carboxy monolith was subjected to post-polymerization modification (PPM) with Tris andd -Glucamine in the presence of N -(3-dimethylamineopropyl)- N ′-ethylcarbodiimide hydrochloride (EDAC), a water soluble carbodiimide. EDAC with its zero-length carboxyl-to-amine coupling ability works by activating the surface carboxyl groups of the monolith for direct reaction with the primary amines of Tris andd -Glucamine via amide bond formation. The Tris-amide (TA) andd -Glucamide ligands imparted the poly(CEA- co -EDMA) monolith a polar character for use in hydrophilic interaction liquid chromatography (HILIC). The TA- andd -Glucamide-poly(CEA- co -EDMA) monolithic capillary columns were evaluated using neutral and charged polar analytes, such as phenolic acids, nucleic acid bases and nucleosides. The difference in polarity between these monolithic capillary columns is noticeable in terms of the numbers of hydroxyl group per ligands, and therefore, thed -Glucamide-poly(CEA- co -EDMA) monolith bearing five hydroxyl groups per ligand could separate more polar species compared to the TA-poly(CEA- co -EDMA) monolith which has three hydroxyl groups per ligand. Solute' retention on both types of HILIC columns were reproducible from run-to-run, day-to-day and column-to-column. Graphical Abstract: